The United Kingdom Childhood Cancer Study: objectives, materials and methods. UK Childhood Cancer Study Investigators. - Boulton, A; Boyd, P; Cheng, K; Cook, J; Gilman, E; Lunt, D; Mahler, H; Walker, C; Wardroper, M; Darbyshire, P; Hill, F; Mann, JR; et al. (2000)
An investigation into the possible causes of childhood cancer has been carried out throughout England, Scotland and Wales over the period 1991-1998. All children known to be suffering from one or other type of the disease over periods of 4-5 years have been included, and control children matched for sex, age and area of residence have been selected at random from population registers. Information about both groups of children (with and without cancer) has been obtained from parental questionnaires, general practitioners' and hospital records, and from measurement of the extent of exposure to radon gas, terrestrial gamma radiation, and electric and magnetic fields. Samples of blood have also been obtained from the affected children and their parents and stored. Altogether 3,838 children with cancer, including 1,736 with leukaemia, and 7,629 unaffected children have been studied. Detailed accounts are given of the nature of the information obtained in sections describing the general methodology of the study, the measurement of exposure to ionizing and non-ionizing radiation, the classification of solid tumours and leukaemias, and the biological material available for genetic analysis.